Literature Study on the Use of Health Applications for Pregnant Women - Nining Sulistyowati (Sean Institute, 2025)
The development of information and communication technology is currently getting faster and faster, almost all aspects of life are related to information and communication technology. Information and communication technology is no longer something new in society because people have widely utilized information technology in carrying out their daily activities. Especially after the discovery of mobile devices such as cellphones, which currently anyone and any group can have. Estimated Fetal Weight is one way to monitor fetal growth in the womb. Along with the development of technology, the use of Android can be used as a medium for educational health information. Determining the beginning of pregnancy and gestational age is important to be able to know the development of the pregnancy. Gestational age can be known, one of which is by knowing the first day of the last menstruation which can be done with an Android-based smartphone application. The purpose of this research plan is to determine the effectiveness of the use of health applications for pregnant women with HPHT and TBJ on the knowledge of pregnant women. The method in this study is a literature study. From several studies/reviews, it was conveyed that there were differences before and after using the application. There was a significant difference in knowledge between before and after the use of the android application was successfully carried out and implemented to the target users, namely pregnant women who use Android-based smartphones. Similar things are in line with the results of the study which also showed that the use of android applications with a p value of 0.000. The application can also improve midwives' knowledge in monitoring fetal growth. Conclusions and suggestions. Health applications are believed to be able to increase knowledge and can monitor fetal weight development and further research is needed for more optimal results.